The decolonial killjoy: the British Raj as a space of political utopia - Ahmed, Ibtisam (2022)
Utopianism and colonialism have an intrinsically linked history. Thomas More’s eponymous Utopia (1516) was a settler colony after all, and the global spread of colonialism carried an ideological justification that had an implicit utopian explanation. The historiography of the British Raj is no exception to this – the Raj represented an ideal society that the colonial powers were trying to create. Whether or not the word was explicitly used when discussing the Raj and the wider British colonial project, there is strong evidence to support the utopian impulse in its implementation, as well as in its rejection.